(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
A 60-day experiment was conducted to compare the accumulation and toxicological effects of arsenic in muscle, intestine and liver of shingi fish, H. fossilis (Bloch) after exposure to two concentrations (7.0 and 20.0 ppm) of arsenic trioxide. The highest/maximum level of accumulation of arsenic was observed in the liver whereas the lowest level of arsenic was found to accumulate in the muscle tissues at the end of exposure period. It is apparent from the study that the damage of the liver of test fish due to 15 days exposed period was less compared to the damage caused by 60 days exposure periods. The intensity of histological alterations was observed to increase gradually with the arsenic concentration and the exposure time. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17861 J. Asiat. Soc. Bangladesh, Sci. 39(2): 221-230, December 2013